Medication Non-adherence and Condomless Anal Intercourse Increased Substantially During the COVID-19 Pandemic Among MSM PrEP Users: A Retrospective Cohort Study in Four Chinese Metropolises - Gao, Yangyang; Hu, Qinghai; Leuba, Sequoia I.; Jia, Le; Wang, Hongyi; Huang, Xiaojie; Chen, Yaokai; Wang, Hui; Zhang, Jing; Chu, Zhenxing; Zhang, Lukun; Wang, Zixin; et al. (Frontiers in Medicine, 2022)
Background: The coronavirus disease (COVID-19) pandemic has impacted HIV prevention strategies globally. However, changes in pre-exposure prophylaxis (PrEP) adherence and HIV-related behaviors, and their associations with medication adherence among MSM PrEP users remains unclear since the onset of the COVID-19 pandemic. Methods: A longitudinal observational study of HIV-negative MSM PrEP users was conducted in four Chinese metropolises from February to March 2020, assessing the changes in PrEP adherence and HIV-related behaviours before and during the COVID-19. The primary outcome was poor PrEP adherence determined from self-reported missing at least one PrEP dose in the previous month. We used mulitivariable logistic regression to determine factors correlated with poor adherence during the COVID-19. Results: We enrolled 791 eligible participants (418 [52.8%] in daily PrEP, 373 [47.2%] in event-driven PrEP). Compared with the data conducted before the COVID-19, the proportion of PrEP users decreased from 97.9% to 64.3%, and the proportion of poor PrEP adherence increased from 23.6% to 50.1% during the COVID-19 (odds ratio [OR] 3.24, 95% confidence interval (CI) 2.62–4.02). While the percentage of condomless anal intercourse (CAI) with regular partners (11.8% vs 25.7%) and with casual partners (4.4% vs 9.0%) both significantly increased. The proportion of those who were tested for HIV decreased from 50.1% to 25.9%. Factors correlated with poor PrEP adherence during the COVID-19 included not being tested for HIV (adjusted odds ratio [aOR]=1.38 [95% CI: 1.00, 1.91]), using condoms consistently with regular partners (vs. never, aOR=2.19 [95% CI: 1.16, 4.13]) and being married or cohabitating with a woman (vs. not married, aOR=3.08 [95% CI: 1.60, 5.95]). Conclusions: Increased poor PrEP adherence and CAI along with the decrease in HIV testing can lead to increases in HIV acquisition and of drug resistance to PrEP. Targeted interventions are needed to improve PrEP adherence and HIV prevention strategies.